2021
DOI: 10.1177/10482911211015676
|View full text |Cite
|
Sign up to set email alerts
|

Union Efforts to Reduce COVID-19 Infections Among Grocery Store Workers

Abstract: Grocery store workers are essential workers, but often have not been provided with appropriate protection during the current pandemic. This report describes efforts made by one union local to protect workers, including negotiated paid sick leave and specific safety practices. Union representatives from 319 stores completed 1612 in-store surveys to assess compliance between 23 April 2020 and 31 August 2020. Employers provided the union with lists of workers confirmed to have COVID-19 infection through 31 Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Growing evidence supports the extent to which consumers changed their shopping behaviours [ 44 ]. Importantly, compliance and enforcement of mask mandates in grocery stores in select American counties is also associated with fewer COVID-19 cases among workers [ 21 ]. Similar to what was reported by Eriksson & Stenius [ 36 ] in Finland, we found that media and participants described customers as largely compliant, with individuals engaging in “careless” behavior as more of the exception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Growing evidence supports the extent to which consumers changed their shopping behaviours [ 44 ]. Importantly, compliance and enforcement of mask mandates in grocery stores in select American counties is also associated with fewer COVID-19 cases among workers [ 21 ]. Similar to what was reported by Eriksson & Stenius [ 36 ] in Finland, we found that media and participants described customers as largely compliant, with individuals engaging in “careless” behavior as more of the exception.…”
Section: Discussionmentioning
confidence: 99%
“…However, the transferability of the findings outside of Canada is likely limited due to different cultural contexts, food systems, social policy (e.g. CERB), and labour unions (see Crowell and colleagues [ 21 ] for evidence regarding associations between unions and COVID-19 cases among grocery workers). In this regard, analysis of union communications may have uncovered additional information regarding COVID-19-related policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-store rates of Covid-19 infections compared to county background rates demonstrated lower than background illness rates in stores with management enforcement of customer mask use and in stores where management was reported to be responsive to worker complaints, among other findings. 2 Ongoing union work focused on vaccination outreach and ventilation, with union representatives using real-time CO2 monitors to assess adequacy of air exchanges. Once again, the union was strongly engaged in vaccination access, negotiating for workers to be prioritized within stores (many of which had pharmacies that were engaged in vaccinating the public before vaccinating workers), as well as using trusted messengers and social media and leading by example.…”
Section: Specific Sectorsmentioning
confidence: 99%
“…A 2020 study in a Massachusetts-based grocery store found that employees who worked in direct customer service jobs had a five-fold increase in the odds of PCR positivity for SARS-CoV-2 when compared to employees who had other job types; 76% of SARS-CoV-2 PCR positive cases were asymptomatic [ 3 ]. Compliance with public health prevention measures, including enforcing mask use in grocery stores and limiting the use and/or contact with reusable bags have been shown to be associated with decreased COVID-19 risk in grocery workers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%